Moderating Effect of Culture on the Relationship of Job Factors with Social and Psychological Characteristics - Ahmed, Sadrudin A. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1978)
This paper explores the relationship between a six-dimensional achievement scale, as well as some socio-economic characteristics and perception of employment assurance, desired job characteristics, income aspiration level and willingness to make an effort for obtaining desired job characteristics by students in the province of Québec.